2022
DOI: 10.1155/2022/4931210
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Observation and Value Analysis of Endovascular Interventional Therapy for Intracranial Venous Sinus Thrombosis

Abstract: The main aim of this study was to investigate the therapeutic effect of endovascular interventional therapy on cerebral venous sinus thrombosis (CVST). 137 patients with CVST were included, 92 patients were treated with interventional therapy, and 45 patients were treated with conventional anticoagulant therapy. Through endovascular therapy (EVT) combined with therapy, the patients were treated with EVT in combination with conventional anticoagulant therapy, and the prognosis of the two groups of patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The technique of interventional therapy with CVST is not mature in some areas of our country. A previous study with a small sample size showed that endovascular treatment may through venous recanalization improve neurological outcomes in most patients with CVST, [18][19][20] while reducing the dose of thrombolytic drugs to decrease the risk of cerebral hemorrhage. This study did not find that interventional therapy had significant benefits in terms of prognosis compared with that observed for patients who did not receive interventional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The technique of interventional therapy with CVST is not mature in some areas of our country. A previous study with a small sample size showed that endovascular treatment may through venous recanalization improve neurological outcomes in most patients with CVST, [18][19][20] while reducing the dose of thrombolytic drugs to decrease the risk of cerebral hemorrhage. This study did not find that interventional therapy had significant benefits in terms of prognosis compared with that observed for patients who did not receive interventional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%